Cultura vicerregia y Estado colonial. Una aproximación crítica al estudio de la historia política de la Nueva España - Cañeque, Alejandro (El Colegio de México, A.C., 2001)
Traditionally, studies on New Spain political history concentrate, on the one hand, on the analysis of the juridical-legal institutions and structures imposed  by  the Spaniards after the conquest, and, on the other hand, on the most relevant viceroys of the 16th century,  those who are thought to have established such structures in New Spain. This study attempts to go beyond that static, monolithic, and clearly restricted view of political realities in 16th and 17th century  New Spain by analyzing the  discourses of prudence, justice, liberality and magnificence, or key concepts and images, such as the viceroy as “the living image of the king” or the “two knives” theory. Thus, examining the defining traits of New Spain’s political culture, and more  specifically, the viceregal  political culture, proves to be a more adequate method to appreciate, in all its complexity, the dinamics of power among New Spain’s elite, both Peninsular and American-born.